EVALUASI PELAKSANAAN PROGRAM PENDIDIKAN INKLUSI DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA KREASI KOTA PEKANBARU - Novita Sari; Daeng Ayub Natuna; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based by not yet done the evaluation of implementation inclusive education program at Community Learning Activity Center (CLAC) Bina Kreasi Pekanbaru City. The formulation of this research problem is whether the inclusion education program at Community Learning Activity Center (CLAC) Bina Kreasi Pekanbaru City has been done well ?. This study aims to determine the assessment of the implementation of inclusive education program at Community Learning Activity Center (CLAC) Bina Kreasi Pekanbaru City. Subjects in this study as many as 15 people consisting of managers, tutors, students, and parents. This research instrument uses documentation, observation, and interview. The study used a CIPP model evaluation of Stufflebeam consisting of four indicators, namely context evaluation, input evaluation, process evaluation, and product evaluation. The result of the research can be concluded that the implementation of inclusive education program at Community Learning Activity Center (CLAC) Bina Kreasi Pekanbaru City is done well.Keywords: Evaluation, Inclusive Education